Early combination treatment with baloxavir and peramivir for hospitalized adults with influenza A in Yokohama, Japan - Yoshimura, Yukihiro; Sasaki, Hiroaki; Horiuchi, Hiroshi; Miyata, Nobuyuki; Kawakami, Chiharu; Usuku, Shuzo; Tachikawa, Natsuo (European journal of clinical microbiology & infectious diseases, 2020)
Baloxavir marboxil is a new anti-influenza drug, but data on the clinical efficacy of a combination treatment of baloxavir and peramivir is scarce. We conducted a single-center retrospective analysis comparing the mortality of a combination of baloxavir and peramivir (B & P, n = 10) and peramivir without baloxavir (P-mono, n = 132) in hospitalized adults with influenza A between 2011 and 2019 in Yokohama City, Japan. Sequencing analysis was conducted in the B & P group to check the I38 mutation in polymerase acidic protein which is associated with baloxavir resistance. The 30-day mortality rates were 0 (0%) in the B & P group and 6 (4.5%) in the P-mono group, respectively, which was not statistically significant. The I38 mutation was not detected before and after the combination treatment. A combination treatment of baloxavir and peramivir might be more effective than peramivir without baloxavir and prevent the emergence of baloxavir resistance in hospitalized adults with influenza A.